Automatic navigation of radio - controlled car using video processing (Car Control) [electronic resource] - 222641 Tan, Yee Sing; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Komputer)) - Universiti Teknologi Malaysia, 2007